Application of Plea Bargaining in Settlement of TPPU Cases with Criminals Originating from TIPIKOR in Efforts to Achieve Justice - Reumi, Frans; Polontoh, Herry (PT. Hafasy Dwi Nawasena, 2024)
At present, money laundering offenses burden the criminal perspective of the institution rather than the return of state finances. This study uses a normative juridical approach to review how the application of plea bargaining in Indonesia, which is a civil law country. The application of plea bargaining is something that needs to be considered immediately in combating corruption through state loss restitution, because with the recovery. The use of the plea bargaining concept is a breakthrough in resolving money laundering offenses to uncover cases that are difficult to solve, as it is carried out in an organized manner. Plea Bargaining is in line with the Draft Law on Criminal Procedure known as the special route.